From Source to Corridor: Changing Geopolitical Narratives about Migration and EU-Western Balkans Relations. Issue 1 (2nd January 2019) - Pastore, Ferruccio
ABSTRACT: The 'refugee crisis' of 2015–2016 brought the 'migration factor' back to the centre of the political agenda in European Union–Western Balkans (WB) relations. But the way in which population movements from and through the region are framed by the EU has changed deeply from the past. After having been seen in the 1990s as the main sending region for irregular and humanitarian migration flows to Western Europe, and following a period of decreasing political attention in the 2000s, the opening of the 'Western Balkans route' for forced migrants from the Middle East turned the region into a 'transit corridor'. Drawing upon literature on the role of policy frames and narratives in migration policy-making, the article reconstructs this evolution, identifying a trend towards narrative simplification based on an essentialized understanding of the relations between migration dynamics and territories. The risks of 'geopolitical determinism' in shaping future strategic choices are pointed out.